Pediatric Ototoxicity: Current Trends and Management - Fligor, Brian J. (Seminars in Hearing, 2019)
Medical interventions to combat serious infection or malignancies carry significant morbidities, including ototoxicity. While these lifesaving drugs are often necessary to preserve life, the impact on quality of life for survivors is increasingly concerning for families and healthcare providers. Of primary importance for medical prescribers are appropriately sensitive ototoxicity grading scales and audiological monitoring protocols for surveillance for hearing loss. The intent of grading scales is to help communicate complicated audiological information to non-audiologist healthcare providers (such as oncologists) to help them make good decisions with regards to chemotherapy dosing. Appropriate audiological monitoring helps reduce the time delay between the adventitious onset of hearing loss and the diagnosis and intervention. Finally, pediatric ototoxicity grading and monitoring protocols help ensure timely access to adequate hearing habilitation, verification and validation of the management of permanent medication-induced hearing loss and tinnitus in children.
Keywords: ototoxicity; cisplatin chemotherapy; aminoglycosides